Syntheses and Properties of Copolymers with N-Alkyl-2,2′-bithiophene-3,3′-dicarboximide Unit for Polymer Solar Cells - Kim, Juae; Kim, Shin Hyun; Kim, Taehyo; Shim, Joo Young; Park, Dongkyung; Kim, Jinwoo; Kim, Il; Kim, Jin Young; Suh, Hongsuk (Bulletin of the Korean Chemical Society, 2015)
We report new random copolymers using the electron‐deficient unit N‐alkyl‐2,2′‐bithiophene‐3,3′‐dicarboximide (BTI) for organic solar cells. For absorption over a broader range of the solar spectrum, push–pull types of conjugated polymers PBTIBDT ‐3, PBTIBDT ‐5, and PBTIBDT ‐7, containing 4,8‐bis(2‐octyldodecyloxy)benzo[1,2‐b;3,4‐b']dithiophene (BDT) as electron‐pushing unit and BTI as electron‐pulling unit, were synthesized. The polymers were synthesized by coupling electron‐pushing and electron‐pulling units by Stille polymerization with Pd(0) catalyst. The incorporation of more BTI units induced more red shift of the absorption spectra of the polymer thin films. The device comprising PBTIBDT ‐5 and PC71BM (1:1) showed V OC = 0.76 V, J SC = 3.28 mA/cm2, and fill factor (FF) = 0.51, giving a power conversion efficiency of 1.26%.